Cyclic test and lateral resistant design of corrugated plate shear walls. (March 2023) - Xie, Cheng; Dou, Chao; Ru, Yi
Abstract: To investigate the lateral resistant behaviour of corrugated plate shear walls (CPSWs), this paper conducted cyclic loading tests on three CPSW specimens with different infill panel configurations and boundary frame rigidities, in which the hysteretic behaviour, failure modes and the boundary column stresses were mainly analyzed. The effect of boundary column rigidity on the infill corrugated panel was then explored by using finite element analysis (FEA), and the design method for optimization of the corrugated panels was proposed. The tests revealed two typical lateral resistant mechanisms of CPSWs, namely in-plane shear yielding and tension field action after buckling respectively. The flexural rigidity demand of the boundary frame can be reduced for infill corrugated panels with the in-plane shear yielding resistant mechanism. To achieve a high-efficiency lateral resistant system, the corrugation profile of the infill panel needs to be properly selected, and the proposed recommendations for CPSWs can achieve in-plane shear yielding mechanism with stable lateral resistance, good ductility and energy dissipation capacity.